Analisis Kinerja Keuangan Melalui Analisis Trend Dan Compound Annual Growth Rate (CARG) Pada PT. Akr Corporindo, Tbk - Nia Janiati; Nurhayati (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
This study was conducted to determine the Analysis Of Financial Performance Through Trend Analysis And Compound Annual Growth Rate (CARG) at PT. AKR Corporindo, Tbk. The research method is using a descriptive method, with a quantitative approach. Data collection techniques using secondary data. The population in this study is 60 years old and the sample used is 10 years which is the annual report of the product distribution sector on the Indonesia Stock Exchange (IDX). The sampling technique used purposive sampling technique. The results of the study using the t-test one sample sales and net income at PT. AKR Corpindo Tbk are said to be good because more than 20%, which means that the value of financial performance at the CAGR level of PT. AKR Corpindo Tbk's revenue is good.